2016
DOI: 10.1007/s11356-016-6591-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic amendment application on mercury-polluted soils: effects on soil chemical and biochemical properties

Abstract: On the basis of a previous study performed in our laboratory, the use of organic and inorganic amendments can significantly modify the Hg mobility in soil. We have compared the effectiveness of organic and inorganic amendments such as digestate and fly ash, respectively, reducing the Hg mobility in Chernozem and Luvisol soils differing in their physicochemical properties. Hence, the aim of this work was to compare the impact of digestate and fly ash application on the chemical and biochemical parameters in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The pH value in soil can strongly change the mobility of mercury by influencing the different presence forms of mercury. As pH increases in soil, the bioavailability and mobility of mercury decreases [46,47,48], and the content of mercury increases, which is in agreement with our results. In the agricultural land, the occurrence of mercury content decreased in TS1, and the second peak in TS5 (Figure 4) was attributed to the influence of pH value change.…”
Section: Resultssupporting
confidence: 91%
“…The pH value in soil can strongly change the mobility of mercury by influencing the different presence forms of mercury. As pH increases in soil, the bioavailability and mobility of mercury decreases [46,47,48], and the content of mercury increases, which is in agreement with our results. In the agricultural land, the occurrence of mercury content decreased in TS1, and the second peak in TS5 (Figure 4) was attributed to the influence of pH value change.…”
Section: Resultssupporting
confidence: 91%
“…The reduction of Pb levels in soil extracts and test plant seeds is proved by the application of these substance (García-Sánchez, García-Romera, Száková, Kaplan, & Tlustoš, 2015). Bioslurry also reduces the toxicity of Hg on soil microorganisms which is proved by the increase of weight and activity of microorganism biomass in amended soil (García-Sánchez, Klouza, Holečková, Tlustoš, & Száková, 2016). Utilization of natural lime-based materials showed that the addition of 1% eggshell and oyster shell can reduce 26.60% Pb in TCLP leachate (Lim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ARS have been key enzymes in the bacterial cell response against S limitation, and they can potentially hydrolyze sulphate esters from environmental sources or from the reserves of the bacterial cell [ 18 , 19 ]. In agriculture, arylsulfatase is one of the enzyme activities used to evaluate the soil biological diversity in natural or burdened ecosystems due to intensive crop systems, application of pesticides, and overdosed fertilization [ 19 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Increased arylsulfatase activity in soils is an indication of plant cultivation and crop rotations [ 31 , 32 , 33 , 34 ] and vice versa; the decrease of arylsulfatase activity in field soil is an indication of metal and pesticides contaminations [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In agriculture, arylsulfatase is one of the enzyme activities used to evaluate the soil biological diversity in natural or burdened ecosystems due to intensive crop systems, application of pesticides, and overdosed fertilization [ 19 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Increased arylsulfatase activity in soils is an indication of plant cultivation and crop rotations [ 31 , 32 , 33 , 34 ] and vice versa; the decrease of arylsulfatase activity in field soil is an indication of metal and pesticides contaminations [ 33 , 34 , 35 , 36 ]. A soil with arylsulphatase microbial activity improves or alters its biological composition by affecting its fertility [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%